Design Considerations for Augmented Reality Supported Tactical Decision Making Systems - Smarr, Simone A.; Davis, Alexis; Traynham, Niya; Abram, Nicholas; Aryal, Saurav K.; Nias, Jaye; Williams, Lucretia; Blackstone, Jeremy; Washington, Gloria (Proceedings of the AAAI Symposium Series, 2026)
In high-stakes environments, tactical decision making iscritical, and managing cognitive load and stress isimportant. The Tactical Decision Making Under Stress(TADMUS) program established a foundation fordecision-support systems grounded in naturalisticdecision-making processes and meaningful informationpresentation. Immersive technologies, like augmentedreality (AR), create opportunities to extend this workwhile introducing new design challenges related tocognitive load and awareness.This research explores the design of an AR decision supportinterface for TADMUS contexts using a human-centered designapproach informed by alert design, augmented reality, anddecision support literature. Focused on alert systems as akey mechanism for communicating time-sensitive informationin spatial computing environments, we identify AR-specificalert design challenges that should be considered andpresent a tiered alerting approach to support tacticaldecision making.